Effect of Changing The Spring Constant of Continuously Variable Transmission On The Performance of Honda Vario 150 cc Motorcycle - Adha, Muhammad Dito; Setiawan, Reza (TRANSMISI, 2025)
This study analyzes one of the components in the Continuously Variable Transmission (CVT) system, namely the CVT spring. The aim of this research is to determine the power, torque, acceleration, and fuel consumption produced by each different CVT spring. The study utilizes an experimental approach by testing four CVT springs with varying spring constants. Each spring was installed on the vehicle and tested using a dynotest to measure the resulting power, torque, acceleration, and engine speed. Fuel consumption tests were conducted through road testing over short and long distances (10 km to 90 km) with a maximum speed of 75 km/h. The test results indicate that each spring generates a different transmission ratio, which affects the resulting power, torque, acceleration, and fuel consumption. The highest maximum power was achieved when using a CVT spring with 20% stiffness, reaching 11.3 hp at 6493 RPM. The maximum torque was obtained with a 10% stiffer CVT spring, reaching 13.1 Nm at 6042 RPM. The highest acceleration was recorded with a 30% stiffer CVT spring, achieving 8.8 m/s² at a speed of 22 km/h in 0.51 seconds. The most efficient fuel consumption was found with the standard CVT spring, both for short and long distances, achieving 47.6 km/L over a short distance of 10 km and 54.7 km/L over a long distance of 90 km.